Analyzing outcomes of the adjustable transobturator male system for post-prostatectomy incontinence and its relationship with detrusor overactivity and radiotherapy with the help of urodynamics - Farag, Samuel; Ismail, Salima; Pelletier, Joanie; Tu, Le Mai (Canadian Urological Association Journal, 2025)
INTRODUCTION: The adjustable transobturator male system (ATOMS) has recently garnered attention for its surgical simplicity and suitability for mild post-prostatectomy incontinence (PPI). This retrospective study investigated the outcomes of patients who received ATOMS, including subgroup analyses of individuals with overactive bladder (OAB) or previous radiotherapy. METHODS: A retrospective cohort study was conducted on 104 patients who received ATOMS. To classify mild, moderate, and severe incontinence, preoperative severity was defined as <2 pads per day (PPD), 2-4 PPD, and >4 PPD, based on the 24-hour pad count and/or <200 g, 200-400 g, and >400 g, based on the 24-hour pad-test (24h-PT). Postoperative “dry” status referred to ≤1 pad/day, while “improved” or “very much improved” indicated a pad reduction of ≥50% or ≥75%, respectively. Patients who reported “much better” or “very much better” on the Patient Global Impression of Improvement-Incontinence (PGI-I) questionnaire were considered “satisfied.” RESULTS: Thirteen patients were excluded for insufficient followup, leaving 91 patients (mean age 70 years, mean followup 42 months). Most were classified as moderately (44%) or severely (55%) incontinent, with a median of four pads/day and a mean 24-hour pad test of 351 g preoperatively. At final followup, the median pad count was 0.5; 89% improved overall, 58% became dry, and 91% were satisfied. Complications occurred in 27% (five grade III). Patients with prior radiotherapy (n=29) exhibited lower dryness (55% vs. 79%) and improvement (83% vs. 92%), alongside more adjustments and higher total instilled volume. There were no other significant subgroup differences. CONCLUSIONS: ATOMS appears to be a safe and effective device for PPI, including for moderate to severe incontinence, although radiotherapy may affect efficacy.